Numerical Simulation of the Microtron Electron Beam Absorption by the Modified ABS-Plastic; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Stuchebrov S. G. Sergey Gennadevich; Miloichikova I. A. Irina Alekseevna; Melnikov A. L.; Pereverzeva M. A. (2016, 2016)
Title screen